In vitro regeneration from protocorms in Dendrobium aqueum Lindley – An imperiled orchid - Selvaraju Parthibhan; Mandali Venkateswara Rao; Thiruppathi Senthil Kumar (Journal of Genetic Engineering and Biotechnology, 2015)
An efficient in vitro plant regeneration protocol from protocorms of Dendrobium aqueum was developed. The uniformly developed protocorms (in vitro origin) having shoot initials were cultured on half macro strength MS medium (1/2 MS) supplemented with cytokinins (BA, 2iP, KIN and TDZ) at 1, 3, 5, 7, 10 mg l−1, natural additives (BP and CW) at 1%, 3%, 5%, 7%, 10% and auxins (IBA, NAA, 2,4-D) at 1, 3, 5, 7, 10 mg l−1 to study their efficacy on complete plant development. A maximum of 9.4 shoots per explant were generated on 3 mg l−1 of NAA followed by 3% of BP (7.0 shoots). Shoot elongation (1.52 cm) was achieved on 1/2 MS medium fortified with NAA 7 mg l−1 followed by TDZ 7 mg l−1 (1.37 cm). Shoots cultured on 1/2 MS medium supplemented with IBA 5 mg l−1 produced an average of 8.75 roots per shoot, however the lengthiest roots (1.48 cm) were noted in NAA 7 mg l−1. Healthy rooted plantlets successfully acclimatized in ex vitro condition. The role of complete plantlet production by natural additives could be useful for conservation and cost effective commercial production of orchids.